Front Cover. Issue 6 (14th November 2018) - Kvarnung, Malin; Taylan, Fulya; Nilsson, Daniel; Anderlid, Britt‐Marie; Malmgren, Helena; Lagerstedt‐Robinson, Kristina; Holmberg, Eva; Burstedt, Magnus; Nordenskjöld, Magnus; Nordgren, Ann; Lundberg, Elisabeth S.
Abstract : The cover image is based on the Original Article Genomic screening in rare disorders: New mutations and phenotypes, highlighting ALG14 as a novel cause of severe intellectual disability, by Malin Kvarnung et al., https://doi.org/10.1111/cge.13448 . Abstract : The cover image is based on the Original Article Genomic screening in rare disorders: New mutations and phenotypes, highlighting ALG14 as a novel cause of severe intellectual disability, by Malin Kvarnung et al., https://doi.org/10.1111/cge.13448 .